Posterior Occipitocervical Fusion for Unstable Upper Cervical Trauma in Old and Elderly Population, Although Decreases Upper Cervical Rotation, Does Not Significantly Increase Neck Disability Index - Panagiotis Korovessis; Vasileios Syrimpeis; Evangelia Mpountogianni; Ioannis Papaioannou; Vasileios Tsekouras (Advances in Orthopedics)
Background. Despite the research progress in the thoraco-lumbo-pelvic balance, cervical spine balance has only recently gained increasing interest. To our knowledge, there is a lack of research regarding sagittal occipitocervical spine balance restoration following posterior occipitocervical fusion (POCF). Purpose. The primary outcome measure is the evaluation of sagittal cervical alignment roentgenographic parameters and the secondary is the functional outcome (NDI), following POCF for upper (C1 & C2) cervical trauma (UCT) in coexistence with upper cervical spine degeneration. Patients and Methods. Twenty old and elderly patients aged 62 ± 12 years with evident upper cervical degeneration, who received POCF for upper C1 & C2 unstable cervical spine injuries, were included. C2-C7 lordosis, C2-C7 SVA, spinocranial angle (SCA), T1-slope, neck tilt (NT), thorax inlet angle (TIA), cervical tilt (CT), cranial tilt (CrT), and C0-C1 angle were measured. The subfusion angle was used to study the behavior of the unfused cervical segments below fusion. The Neck Disability Index (NDI) was used for the functional outcome evaluation. 29 age-matched individuals were used as controls for radiographic analysis and self-reported functional status comparison. Results. The roentgenographic data were measured 3 and 39 ± 12 months postoperatively. Twelve patients showed no disability, and eight showed mild disability. Postoperatively, the patients stood with less C2-C7 lordosis, SCA, and CT (P<0.02) but with higher NT (P<0.02) in comparison to the controls. The patient’s neck disability (NDI) was increasing as TIA increases (P=0.023). Subfusion angle seems to adapt to C2-C7 lordosis (P<0.0033) and C0-C2 angle (P<0.003) without any changes till the last evaluation. Conclusions. POCF sufficiently restored occipitocervical sagittal balance along with functional outcome similar to controls in adult and elderly individuals with evident upper cervical degeneration. We do not recommend POCF for young active individuals without occipitocervical pathology, but in contrary, we recommend the removal of the spinocranial connection hardware after cervical fusion is completed.